Apixaban versus warfarin in nephrotic syndrome: thromboembolic events, bleeding risk and changes in profibrotic and inflammatory cytokines - I. Mykhaloiko; R. Yatsyshyn (Ukrainian Journal of Nephrology and Dialysis, 2026)
Nephrotic syndrome (NS) is associated with a high risk of thromboembolic complications and activation of inflammatory and profibrotic pathways. The optimal anticoagulation strategy in NS remains uncertain.Objective. To compare the efficacy and safety of apixaban versus warfarin in patients with NS and to explore their effects on inflammatory, profibrotic, and coagulation biomarkers.Methods. In this prospective observational cohort study, 67 adults with biopsy-proven primary glomerulonephritis and newly diagnosed NS were followed for 6 months. Patients received either warfarin (n=33) or apixaban (n=34) for thromboprophylaxis. Primary endpoints were thromboembolic and bleeding events. Secondary endpoints included longitudinal changes in serum and urinary IL-6, TNF-α, TGF-β₁, thrombin, proteinuria, and estimated glomerular filtration rate (eGFR).Results. No thromboembolic events occurred in either group. Bleeding events were more frequent with warfarin (33.3%) than with apixaban (8.7%) (OR 5.17, 95% CI 1.28–20.9; p=0.021); all were minor. Both treatments were associated with reductions in inflammatory and profibrotic markers; however, apixaban demonstrated earlier and more pronounced decreases in serum and urinary IL-6, TNF-α, TGF-β₁, and urinary thrombin (all p<0.05 at 6 months vs warfarin). Proteinuria declined in both groups but was significantly lower in the apixaban group at 6 months (p=0.026). Decline in eGFR was less pronounced with apixaban (p=0.035 between groups).Conclusions. Apixaban provided effective thromboprophylaxis with fewer bleeding events than warfarin and was associated with greater reductions in inflammatory and profibrotic biomarkers, alongside more favorable changes in proteinuria and eGFR. These findings suggest potential beneficial pleiotropic effects for apixaban requiring confirmation in randomized studies.